Uji Signifikansi Distribusi T - Sabiru, Tri; Al ‘Auni, Khofifah; Panggabean, Hadi Saputra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The t-Student distribution is an important tool in statistical analysis, especially for hypothesis testing and determining confidence intervals on small samples. Introduced by William Sealy Gosset, this distribution excels at accommodating greater uncertainty than the normal distribution, making it ideal when the population standard deviation is unknown. This research uses the literature study method to explore the characteristics of the t distribution and its applications in various fields, including psychology, medical, and education. The t-test procedure involves setting the hypothesis, calculating the t value, and determining the critical value, which helps the researcher in making statistical decisions. The t-test results provide significant insights into the differences between groups and relevance in designing more effective teaching strategies. Further research is needed to explore the potential of the t distribution in wider applications and develop more innovative methods of analysis.